Acquired Inhibitors of Coagulation Factors: Part II - Franchini, Massimo; Lippi, Giuseppe; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2012)
Acquired coagulation inhibitors are antibodies that bind to coagulation factors and neutralize their activity or accelerate their clearance. Inhibitors occurring in patients with inherited deficiencies of coagulation factors are referred to as “alloantibodies,” while those developing spontaneously in individuals with previously normal coagulation factor function are designated as “autoantibodies.” The latter category includes inhibitors against coagulation factors I, II, V, VII, VIII (acquired hemophilia A), IX (acquired hemophilia B), X, XI, and XIII. This review will discuss the most important pathogenic, clinical, laboratory, and therapeutic aspects of the inhibitors of coagulation factors other than acquired hemophilia A, as this is reviewed separately within this issue of the journal.
Keywords: acquired hemophilia; inhibitors; autoantibodies; bleeding